Monitoring Eastern Imperial Eagle in the Khvalynsky National Park (Saratov Region, Russia) - Andrey V. Belyachenko (Пернатые хищники и их охрана)
The special structure of breeding territories, breeding parameters, and nutrition of the Eastern Imperial Eagle (EIE, Aqula heliaca) were studied in 2019–2023 in conservation (1,400 hectares), recreational (3,600 hectares), economic (20,600 hectares), and protective (114,900 hectares) areas of the National Park. 32 breeding territories were identified, 53 nests were discovered (including replacements and those newly build after old nests were destroyed), and the annual breeding of 17–26 pairs was established. In the rearing season, food remains and pellets were collected under 24 nests and 15 perches, and 4 occupied nests that had fallen from the trees were completely dismantled.